The Influence of Inclusive Education on Students’ Social Skills and Self-Esteem at SDN 1 Gereneng in the Academic Year 2025/2026 - Ria Indriani; Andi Sulastri; Muhammad Husni; Yul Alfian Hadi (MODELING: Jurnal Program Studi PGMI, 2025)
This study investigates the influence of inclusive education on students’ social skills and self-esteem at SDN 1 Gereneng in the 2025/2026 academic year. Using simple linear regression analysis, the findings demonstrate that inclusive education significantly predicts both variables, with 89.1% of the variance in social skills (F = 69.729; p < 0.05; R² = 0.891) and 92% of the variance in self-esteem (F = 97.562; p < 0.05; R² = 0.920) explained by its implementation. The results indicate that inclusive educational practices not only enhance students’ collaboration, empathy, responsibility, and self-regulation in social interactions but also strengthen their confidence and sense of self-worth. Theoretically, this research contributes to educational psychology by affirming the role of inclusive environments in fostering both social competence and self-esteem. Practically, it highlights the importance of designing learning strategies, extracurricular activities, and school climates that balance cognitive, affective, and social dimensions. These findings suggest that inclusive education provides a critical foundation for developing equitable, supportive, and diversity-affirming learning environments that nurture students’ holistic growth.